A novel transthyretin/STAT4/miR-223-3p/FBXW7 signaling pathway affects neovascularization in diabetic retinopathy. (1st December 2019) - Shao, Jun; Fan, Guangming; Yin, Xiaowen; Gu, Yu; Wang, Xiaolu; Xin, Yu; Yao, Yong
Abstract: MicroRNAs (miRNAs) are small RNAs without protein-coding functions that negatively regulate target genes and play important roles in physiological and pathological processes. The aim of this work was to reveal a novel miRNA/gene pathway in diabetic retinopathy (DR). A microarray was used to screen miRNAs in samples from nondiabetic controls and patients with DR, and miR-223-3p was screened as a potential candidate. Quantitative real-time PCR (qRT-PCR) revealed that the level of miR-223-3p was frequently overexpressed in DR samples and human retinal endothelial cells (hRECs) in hyperglycemia, but it was decreased in hyperglycemia after the addition of transthyretin (TTR). In addition, according to cell proliferation, tube formation, and wound healing assays, the downregulation of miR-223-3p suppressed cell migration and proliferation, whereas miR-223-3p upregulation showed the opposite effects. Furthermore, luciferase assays identified F-box and WD repeat domain-containing 7 (FBXW7) as a target mRNA of miR-223-3p. High glucose conditions facilitated the recruitment of signal transducer and activator of transcription 4 (STAT4) and promoted the transcription of miR-223-3p. In hRECs, in a hyperglycemic environment, TTR inhibited STAT4 expression, downregulated the level of miR-223-3p, and finally promoted FBXW7 expression. This study found a novel mechanism whereby TTR might affect neovascularization through a newly identified STAT4/miR-223-3p/FBXW7 cascade in DR. Highlights: MiR-223-3p plays key roles in the development of diabetic retinopathy (DR). MiR-223-3p targeted F-box/WD repeat-containing protein 7 gene ( FBXW7 ) mRNA directly, and reduces the expression of FBXW7. STAT4 recognizes mir223-3p as the direct target, and it could enhance the expression of mir223-3p. TTR affects proliferation, migration and tube formation of hRECs in hyperglycemia through TTR/STAT4/mir223-3p/FBXW7 pathway.